Pengaruh Kualitas Pesan Iklan dan Daya Tarik Iklan terhadap Efektivitas Iklan dan Implikasinya pada Brand Awareness - Junita, Junita; Erdiansyah, Rezi (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
The low level of visits to the JD.id site indicates the low level of public awareness of JD.id. This study was conducted to see whether the quality of the advertising message and the attractiveness of the advertisement had a direct or indirect effect on the effectiveness of advertising in increasing JD.id's brand awareness. This research focuses on the JD.id advertisement with the version